PERSEPSI PESERTA DIDIK KELAS X TERHADAP EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) PADA MATA PELAJARAN BIOLOGI SMA NEGERI KIE - Cindi Yuana Selan; Paulus Taek; Mbing M. Imakulata; Moses K. Tokan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to explore the perceptions of tenth-grade students regarding the effectiveness of the Problem-Based Learning (PBL) model in Biology classes at SMA Negeri Kie. Employing a descriptive quantitative method, the research focuses on analyzing students' responses across six key indicators of PBL implementation. The findings reveal that the indicator of PBL application in Biology learning received a response rate of 84%, the influence of PBL on learning motivation reached 81%, active participation and engagement scored 80%, problem-solving skills were rated at 78%, the impact on learning outcomes reached 79%, and the influence on overall involvement and activity was 78%. The average response across all indicators was 80%, indicating that students' perceptions of the effectiveness of the PBL model fall into the